Belanja Oportunistik Pemerintah Daerah pada Masa Pemilihan Kepala Daerah di Indonesia (Studi pada Pemilihan Kepala Daerah Non-Jawa) - Ar Rozi Abdullah; Payamta Payamta (Universitas Pendidikan Ganesha, 2021)
This article analyses opportunistic behaviour of local government spending in period the elections for non-Javanese local heads in Indoensia which have variability in financial performance. Previous studies have shown that the opportunistic behaviour of regional spending is closely related to the holding of local head elections and the presence of incumbents running for reelections. The effect of election and the existence of incumbents in elections on local government spending is tested using a set of panel data for the 2015-2018 period. A total of 858 observation units were tested, consisting of political and financial factors in the pre-election year, election year, and post-election year. Based on the results of regression testing, it is found that evidence of non-Javanese local government spending is opportunistic around local head elections. This condition is indicated by the increase in Grant and Financial Assistance Expenditures, which are discretionary spending. This evidence confirms some previous research on opportunistic spending behaviour around local head elections.